Avaliação clínica e microbiológica da secreção conjuntival em usúarios de prótese ocular em resina acrílica - Neves, Ana Christina Claro [UNESP] (2000)
The purpose of this work was to evaluate the bacterial and fungic microbiota of the anophthalmic sockets, ocular prosthesis and fellow eyes of forty three acrylic resin prosthesís carrying patients, and thereby relate the amount of conjunctival discharge to the presence of organisms, frequency of prosthesis cleaning, time of use and elapsed time since the last prosthesis polishing. All patients showed conjunctival discharge and Gram positive organisms in the anophthalmic sockets. The predominant organisms in the anophthalmic sockets were Staphylococcus coagulase negative, Staphylococcus aureus, Candida albicans, Proteus mirabilis, Citrobacter koseriana, Streptococcus pyogenes, Pseudomonas aeruginosa, Enterobacter sakazakii e Enterobacter aerogenes. Gram negative bacteria were found in eight anophthalmic sockets and fungi in three. No relation was found between the amount of the conjunctival discharge and the presence of Gram negative bacteria in the anophthalmic socket, nor with the frequency of prosthesis cleaning. However, there was a significant relation between the amount of conjunctival discharge and time of prosthesis use, as well as time elapsed since the last prosthesis polishing